2022
DOI: 10.1073/pnas.2113388119
|View full text |Cite
|
Sign up to set email alerts
|

No link between population isolation and speciation rate in squamate reptiles

Abstract: Rates of species formation vary widely across the tree of life and contribute to massive disparities in species richness among clades. This variation can emerge from differences in metapopulation-level processes that affect the rates at which lineages diverge, persist, and evolve reproductive barriers and ecological differentiation. For example, populations that evolve reproductive barriers quickly should form new species at faster rates than populations that acquire reproductive barriers more slowly. This exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 134 publications
(172 reference statements)
2
19
0
Order By: Relevance
“…A positive link between genetic differentiation and speciation rates has been shown in lineages such as birds and fish [13,76]. However, despite being extensively predicted by theory, there is no evidence of such link in orchids, sea snakes or reptiles in general [77][78][79][80], suggesting that in some lineages, other processes independent of genetic differentiation might promote or limit reproductive isolation. To our knowledge, no studies have explicitly tested for a link between genetic differentiation and speciation rates in amphibians, but our results offer indirect evidence.…”
Section: Discussionmentioning
confidence: 98%
“…A positive link between genetic differentiation and speciation rates has been shown in lineages such as birds and fish [13,76]. However, despite being extensively predicted by theory, there is no evidence of such link in orchids, sea snakes or reptiles in general [77][78][79][80], suggesting that in some lineages, other processes independent of genetic differentiation might promote or limit reproductive isolation. To our knowledge, no studies have explicitly tested for a link between genetic differentiation and speciation rates in amphibians, but our results offer indirect evidence.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies (Harvey et al, 2017;Singhal et al, 2022) showed high variation in the estimation of speciation rates across a F I G U R E 5 Scatterplots showing the relationship between log slope (β IBD for GBS and genetic distance over space for mtDNA) for log speciation rate estimates from CLaDS and DR for taxa with more than four samples. The former two methods model rates of speciation using the entire tree structure and therefore may be detecting overall trends better than the DR method.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially powerful approach for disentangling incipient from exhausted radiations would comprise integrating phylogenetic and range data with information on genetic structure of individual species. Past efforts in this direction were often limited by the resolution of population genetic data 21,64 or by spatial and phylogenetic extent they were covering 65 . However, the fast development of genomics promises the future possibility of identifying centres of incipient diversification globally, using the population-level genetic data.…”
Section: Discussionmentioning
confidence: 99%